1982
DOI: 10.1063/1.93584
|View full text |Cite
|
Sign up to set email alerts
|

Lateral epitaxial overgrowth of GaAs by organometallic chemical vapor deposition

Abstract: Lateral epitaxial overgrowth of GaAs by organometallic chemical vapor deposition has been demonstrated. Pyrolytic decomposition of trimethylgallium and arsine, without the use of HCl, was used to deposit GaAs on substrates prepared by coating (110) GaAs wafers with SiO2, then using photolithography to open narrow stripes in the oxide. Lateral overgrowth was seeded by epitaxial deposits formed on the GaAs surfaces exposed by the stripe openings. The extent of lateral overgrowth was investigated as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…In particular, we have found that on precisely oriented (100) GaAs substrates the line seeds aligned 15 o , 30 o , 60 o or 75 o off from the <011> direction should be used to obtain a large value of the lateral to normal growth rate ratio. This finding is in agreement with the results published elsewhere [4,5,[9][10][11].…”
Section: Mechanism Of Elo Growth By Liquid Phase Epitaxysupporting
confidence: 95%
“…In particular, we have found that on precisely oriented (100) GaAs substrates the line seeds aligned 15 o , 30 o , 60 o or 75 o off from the <011> direction should be used to obtain a large value of the lateral to normal growth rate ratio. This finding is in agreement with the results published elsewhere [4,5,[9][10][11].…”
Section: Mechanism Of Elo Growth By Liquid Phase Epitaxysupporting
confidence: 95%
“…Many III/V semiconductor applications require epitaxial growth on patterned (non-ideal) substrates including epitaxial lateral overgrowth [1,2], formation of low-dimensional structures [3,4], and v-grooved lasers [5,6]. Growth on patterned substrates can also be used for investigating fundamental surface processes occurring during epitaxial growth [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, increasing the GaAs thickness from 1.0 to 2.0 mm on the patterned Si actually decreases the stress and in plane strain to 0.7 amd 5.7 Â 10 À4 , respectively. We surmise this strain relief is accomplished in a manner similar to epitaxial lateral overgrowth (ELO), where laterally grown material is demonstrated to result in improved material qualities [43].…”
Section: Article In Pressmentioning
confidence: 98%